2021
DOI: 10.1079/pavsnnr202116013
|View full text |Cite
|
Sign up to set email alerts
|

Biological control of desert locust ( Schistocerca gregaria Forskål)

Abstract: Desert locust (Schistocerca gregaria Forskål) is one of the most serious agricultural pests in the world due to its voracity, speed of reproduction, and range of flight. We discuss the current state of knowledge on its biological control using microorganisms and botanical extracts. Metarhizium flavoviride was among the first fungus to be recognized as a bio-control agent against desert locust in the laboratory and field conditions. Nevertheless, its oil formulation adversely affected non-target organisms, henc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…For example, non-climatic drivers of yield decline need moderate to high resolution satellite data to capture field-level decline in leaf area index resulting from infestation [19]. The impact of pests such as the desert locust [20] and fall armyworm [21] can be countered with cost-effective solutions such as integrated pest management [22] coupled with new resistant crop varieties and targeted biological control agents, such as the use of Metarhizium flavoviride fungus as a control agent for the desert locust [20]. Metrics focused on…”
Section: Earth Observation Data On Agriculturementioning
confidence: 99%
See 1 more Smart Citation
“…For example, non-climatic drivers of yield decline need moderate to high resolution satellite data to capture field-level decline in leaf area index resulting from infestation [19]. The impact of pests such as the desert locust [20] and fall armyworm [21] can be countered with cost-effective solutions such as integrated pest management [22] coupled with new resistant crop varieties and targeted biological control agents, such as the use of Metarhizium flavoviride fungus as a control agent for the desert locust [20]. Metrics focused on…”
Section: Earth Observation Data On Agriculturementioning
confidence: 99%
“…For example, non-climatic drivers of yield decline need moderate to high resolution satellite data to capture field-level decline in leaf area index resulting from infestation [19]. The impact of pests such as the desert locust [20] and fall armyworm [21] can be countered with cost-effective solutions such as integrated pest management [22] coupled with new resistant crop varieties and targeted biological control agents, such as the use of Metarhizium flavoviride fungus as a control agent for the desert locust [20]. Metrics focused on raising yields must be able to capture climatic, economic and social outcomes of investment and changes of policy through time [23], and show clearly how new agriculture management strategies, technology and interventions can counter these pests while still reducing poverty and food insecurity (Table S1) [12].…”
Section: Earth Observation Data On Agriculturementioning
confidence: 99%
“…To overcome the challenge of geographical remoteness and expansive landscape, the FAO Locust Pesticide Referee Group (LPRG) recommended use of ultra-low volume (ULV) formulated pesticides (FAO, 2021). However, Githae and Kuria (2021) found that ULV pesticides resulted in adverse effects on non-target organisms thus threatening the environment. This environmental risk is associated with use of hazardous petroleum products such as diesel, to carry the active ingredient in ULV pesticides, as a cheaper alternative to plant-based oils.…”
Section: Introductionmentioning
confidence: 99%
“…However, the control of desert locusts can have negative ecological consequences on non-target organisms [18][19][20]. Organophosphates and carbamates have historically been the most commonly used insecticides as they are fast acting and relatively non-persistent [16].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Metarhizium anisopliae var. acridum is a biopesticide specific to the family Acrididea, containing desert locusts [20]. However, despite the benefits in minimising the ecological consequences of desert locust control, Metarhizium anisopliae is often not used due to slow action, variable locust mortality and challenges in its production and storage [16].…”
Section: Introductionmentioning
confidence: 99%